Why Some Firms Train Apprentices and Many Others Do Not - Stefan C. Wolter; Samuel Mühlemann; Juerg Schweri (Institute for the Study of Labor (IZA), 2003)
The latest study investigating the cost-benefit ratio of apprenticeship training for Swiss companies has shown that most apprentices offset the cost of their training during their apprenticeship on the basis of the productive contribution of the work they perform. Given this outcome, it is worth investigating why so many firms choose not to train apprentices. Maximum likelihood selection models were used to estimate the net cost of training for firms without an apprenticeship programme. The models show, firstly, that non-training firms would incur significantly higher net cost during the apprenticeship period if they would switch to a training policy and secondly, that this less favourable cost-benefit ratio is determined less by cost than by absence of benefit. For the apprenticeship system as such the results indicate, that as long as training regulations and the market situation permit a cost effective training of apprentices, companies do not need specific labour market regulations or institutions to offer training posts. In this respect, the Swiss findings might be of interest for the on-going German discussion about the expected repercussions of a more general labour market deregulation on the apprenticeship training system.
Keywords: J44; J31; J24; 330; apprenticeship training; firm-sponsored training; cost-benefit analysis; Betriebliche Berufsausbildung; Kosten-Nutzen-Analyse; Auszubildende; Arbeitsproduktivität; Berufsbildungspolitik; Schätzung; Schweiz